A Molecular Transformer: A π‐Conjugated Macrocycle as an Adaptable Host. Issue 21 (12th April 2021) - Wang, Junting; Ju, Yang‐Yang; Low, Kam‐Hung; Tan, Yuan‐Zhi; Liu, Junzhi
Abstract: Here, we report a facile method to synthesize a series of macrocycles with different conformations. The planar macrocycle dimer (1 ), twisted macrocycle trimer (2 ) and "figure‐eight" tetramer (3 ) are clearly elucidated by X‐ray single‐crystal analysis, in which the electron‐rich phenanthrene units offer the possibility of supramolecular assembly. As expected, in the solid state, 1 and 3 assemble into a columnar stack and an interlocking dimer, respectively, via π–π interactions between the phenanthrene units. Compared to the rigid conformation of dimer 1, the structure of tetramer 3 is more flexible due to its enlarged ring size. 3 can deform from a figure‐eight into a boat‐shaped geometry to host a planar electron‐deficient guest using its electron‐rich phenanthrene units. When assembled with spherical electron‐deficient C60, interestingly, 3 further undergoes a conformational transformation from a figure‐eight to a belt shape in order to host C60 . These supramolecular assembly behaviors of 3 demonstrate that it is an adaptable macrocyclic host for both planar molecules and fullerenes. Abstract : Molecular Transformer: A flexible π‐conjugated, all carbon‐based "figure‐eight" macrocycle (3 ) without a meso bridge was synthesized in one step. The supramolecular assembly behavior of 3 was investigated in this work; compared to the rigid conformation of dimer 1, the structure of tetramer 3 is more flexible due to its larger ring size, which endows it with the ability to adjust its conformation according to changes in the external environment.